Formulation and Structural Properties of Textured Vegetable Proteins Balls using Polydextrose - Nguyet T. M. Nguyen; Vy T. T. Vu; Phuong N. T. Dao (Chemical Engineering Transactions, 2023)
The increasing global population accelerates environmental degradation, contributes to global warming, reduces agricultural land, and causes food shortages. Developing products that can reduce dependence on animal husbandry and ensure global carbon neutrality is necessary. This study aimed to create TVP (Textured Vegetable Proteins) meatballs with Polydextrose (PDX) supplementation. The fixed ingredient composition per 100 g was as follows: 70 g ISP (Soy Protein Isolate), 26 g soybean powder, 5 g HVP (Hydrolyzed Vegetable Protein), 4 g soybean oil, and 2 g salt. Added water content was 200 % (by weight). Additives and structural components used include PDX and wheat gluten. Structural properties such as texture, moisture, and water absorption capacity of the formulations have been performed. With 16 % gluten content and 0.9 % polydextrose, the TVP meatballs have a stable structure. This study provided knowledge on how to process alternative meat products that can reduce the burden on animal husbandry and protect the environment.